St.Clair Avenue, Port of Spain, Trinidad - (:unkn) unknown (My University, 2010)
St.Clair which was originally part of a large sugar estate, was developed for housing and some of the affluent homes in the Port of Spain area are located here. In this postcard palm trees overlook some of these homes.
Colour: Black and white; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--St. Clair